Konstruksi Konsep Tarbiyah al-Aulād dalam Literatur Arab Perspektif Ulwan dan Suwaid - Artini, Aisyah Fajar Putri; Kartimi, Kartimi; Hidayat, Ade (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the construction of the concept of tarbiyah al-aulād (child education) in contemporary Arabic literature through a comparative study of two prominent figures, 'Abdullah Nāṣiḥ 'Ulwān and Muḥammad Nūr 'Abd al-Ḥāfiẓ Suwaid. Using a qualitative library research method, this study analyzes primary sources, namely Tarbiyat al-Aulād fī al-Islām by 'Ulwān and Manhaj al-Tarbiyah al-Nabawiyyah li al-Ṭifl by Suwaid, as well as relevant secondary sources.  Data were collected through documentation techniques, involving systematic reading, reviewing, and recording of relevant library materials from both primary and secondary sources. Data analysis employed three complementary methods: content analysis to identify key themes and arguments related to tarbiyah al-aulād; comparative analysis to systematically examine similarities and differences in the conceptual constructions of the two figures; and critical analysis to evaluate the strengths and limitations of each approach objectively. The analytical process followed three stages: data reduction, data presentation, and conclusion drawing, with source triangulation applied to ensure the validity and reliability of the findings. The findings reveal that both figures share a foundational epistemological basis rooted in the Qur'an and Sunnah, yet differ significantly in emphasis and methodological approach. 'Ulwān constructs a comprehensive and systematic framework covering faith, moral, physical, intellectual, psychological, social, and sexual education, whereas Suwaid places greater emphasis on the prophetic model (manhaj nabawī) as the primary reference in child-rearing practices. The comparative analysis shows that 'Ulwān's approach is more encyclopedic and prescriptive, while Suwaid's is more narrative and contextual, drawing heavily from prophetic traditions. Both contribute meaningfully to contemporary Islamic educational discourse. This study concludes that integrating both perspectives offers a more holistic and balanced model of Islamic child education applicable to modern Muslim families.